Nonoperative management after neoadjuvant therapy for rectal cancer: A single institution experience over 5 years. (March 2019) - Strode, Matthew; Shah, Rupen; Boland, Patrick M.; Francescutti, Valerie A.; Mangieri, Christopher W.; Attwood, Kristopher; Nurkin, Steven J.
Abstract: Background: Nonoperative or "watch and wait" strategies have emerged as a potential option for patients with rectal cancer that obtain a complete clinic response (cCR) after neoadjuvant therapy. We sought to evaluate our patients that experienced a cCR and their outcomes after non-operative management. Methods: We performed a retrospective review of patients at our center with rectal cancer from 2012 to 2016. We then identified patients that had a documented "complete clinical response" of their tumors after different neoadjuvant treatments and underwent non-operative management. Patients were followed on a surveillance schedule that included physical exam, endoscopy and imaging. Results: A total of 29 patients elected to undergo nonoperative management with a mean patient age of 67 years old. All patients were treated with neoadjuvant long course chemoradiotherapy. Seven patients were treated with initial induction chemotherapy followed by chemoradiation and 11 received consolidation chemotherapy. During a median follow-up of 27.6 months, there were 6 (21%) recurrences (1 = local, 1 = local and distant, 4 distant). Of the 6 total recurrences, 5 patients were candidates for salvage surgical resection. Conclusion: Neoadjuvant treatment strategies may facilitate durable rates of cCR. Continued responses after these treatments could possibly enable more patients to undergo nonoperative management. We believe nonoperative management can be offered to patients seeking rectal preservation, but more research is required to select the appropriate patients. For those patients experiencing recurrence, the majority of patients can be salvaged surgically.